2016
DOI: 10.1093/humrep/dew235
|View full text |Cite
|
Sign up to set email alerts
|

Autologous menstrual blood-derived stromal cells transplantation for severe Asherman's syndrome

Abstract: Registered in the Chinese Clinical Trial Registry (ChiCTR-ONB-15007464).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
136
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(141 citation statements)
references
References 35 publications
3
136
1
1
Order By: Relevance
“…Recent preclinical studies have also evaluated their therapeutic effects in murine models of pulmonary fibrosis (Zhao et al, 2018), and experimental colitis (Lv et al, 2014). In addition, a recent clinical trial using autologous menstrual blood-derived stromal cells have shown satisfactory results for the treatment of severe Asherman's syndrome (Tan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent preclinical studies have also evaluated their therapeutic effects in murine models of pulmonary fibrosis (Zhao et al, 2018), and experimental colitis (Lv et al, 2014). In addition, a recent clinical trial using autologous menstrual blood-derived stromal cells have shown satisfactory results for the treatment of severe Asherman's syndrome (Tan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Autologous menstrual blood-derived stromal cells transplantation has been proposed as potential option for treating severe AS patient: in a study involving seven AS patients, the Authors isolated autologous stromal cells from menstrual blood and then transplanted them into the uterus. The results showed a significant increase in endometrial thickness (up to 7 mm in 5 women) and this could improve embryo implantation efficiency (51). Endometrial Atrophy (EA) has the same effects and reproductive outcome as AS.…”
Section: Asherman's Syndrome (As) and Endometrial Atrophy (Ea)mentioning
confidence: 98%
“…Although in their infancy, pilot clinical trials with endometrial‐derived stromal cell sources have proven safety and potential efficacy. Tan et al delivered in vitro expanded autologous menSCs to a cohort of 7 women with severe AS. The study reports an increased endometrial thickness as measured by ultrasound, and three conceptions after one or more rounds of cell therapy.…”
Section: Clinical Trials Piloting Cell Therapymentioning
confidence: 99%